IDENTIFYING THE DOMINANT FACTOR OF EDUCATIONAL SERVICE QUALITY FOR THE FACULTY OF ECONOMICS AT MALIKUSSALEH UNIVERSITY - Naufal Bachri; Jullimursyida Ganto; Ahmad Azmi M. Ariffin; Azhar Hj. Ahmad (Indonesian Management and Accounting Research, 2010)
This study seeks to identify the dominant factor of educational service quality that influences the student satisfaction. This study was carried out at Faculty of Economics, Malikussaleh University in Indonesia involving five departments such as economics, management, business, accounting and secretarial. Only a total of 213 questionnaires were collected. The instruments were modified from Educational Service Quality (ESQ) model by Holdford and Patkar. SPSS (version 12.0) was used to run the data gathered. The exploratory factor analysis for students' response of educational service quality created five dimensions namely; facilities, faculty interpersonal behavior, faculty expertise, faculty communication and administration. The multiple regressions analysis showed that all dimensions simultaneously influenced students' satisfaction with a strong correlation. The t-test in the regression analysis indicated that the faculty communication dimension was the dominant dimension which influenced students' satisfaction whereas the interpersonal behavior dimension did not influence significantly the student& satisfaction. Thus, the Faculty needs to focus on employees' improvement because employees' satisfaction would influence students' satisfaction. Besides training to improve the knowledge and skills of employees, work motivation was also a key element that had to be considered by the Faculty of Economics.Keywords: educational service quality and satisfaction